Pendidikan Islam Pada Masa Kemunduran Periode Pertengahan - Y, Yulianti; Rama, Bahaking (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Islamic education during the decline of the medieval period, which lasted from the 13th to the 18th centuries, was marked by intellectual stagnation, the weakening of centers of learning, and the dominance of conservative traditions in Islamic thought. Factors that caused this decline included foreign invasions, such as the Mongol invasion that destroyed Baghdad in 1258, the weakening of Islamic political power, and reliance on traditional teaching methods such as memorization without critical understanding. Nevertheless, Islamic education continued to play an important role in maintaining the tradition of learning and spirituality through institutions such as the madrasah. Madrasahs during this period focused more on the study of Islamic jurisprudence and religious sciences, so they paid less attention to rational sciences such as philosophy, astronomy, and medicine, which had previously flourished during the Golden Age of Islam.